Rancang Bangun Pembangkit Listrik Tenaga Air Jenis Turbin Pelton Skala Laboratorium Sebagai Media Pembelajaran - Hasbi Assiddiq S; Jeffry Anggara; Hairul Anwar (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
The power plant type turbine pelton of scale laboratory was made to be used as a practical medium of students and lecturers of mechanical engineering in the environment Politeknik of Kotabaru. The purpose of this research was to obtain an ideal design for hydropower systems as learning media; Knowing the effect of the lamp load on the generator rotation, knowing the effect of the type of 12 VDC and 24 VDC lamp loads with varying loads on the generator power output. The method used in this study is a literature study and experimental methods. The research results obtained are the design has a table height of 90 cm and a width of 100 cm, the height of the loading panel is 80 cm, the air pressure from the pump is 270 psi with a nozzle size of 1,7 mm, a 12 blade Pelton turbine, a 36 V 60 A DC generator; the type of lamp load affects of generator rotation where when the type of load is 12 VDC the generator rotation is smaller than when the lamp load is 24 VDC, while the large lamp load given to the system causes of generator rotation to decrease or the effect of the lamp load on generator rotation is inversely proportional; the greater of lamp load lower the output power of generator, both with 12 VDC and 24 VDC load types or in other words, it is also reversed.